Coronary heart disease epidemiology: global context for a new genetic understanding - Hemingway, Harry (Henry Stewart Talks, 2008)
Established importance of environment factors, CVD burden increasing globally, Rapid within generation increase in CVD mortality rates, The epidemiological transition, Stages of epidemiological transition and CVD, Where in the world are most CHD deaths occurring?, Within and between country geographical variations, Age is the strongest risk factor for CVD, CHD deaths by social class, Interheart, Obesity trends, We know how to prevent CHD, Shifting the population distribution of risk, Possible relevance of genes, Large scale epidemiological evidence, Deaths by cause in women, Coronary phenotypes, Angina trends, Evidence from Finland, Genome-wide association studies, Phenotypes in WTCCC GWAS, Genetic influences on smoking behavior, Genotype and smoking quantity, Phenotypically differentiating chronic and acute syndromes of coronary disease is likely to be important, Interplay between identified genetic variants and environmental exposures in large scale studies: watch this space